Analysis and Classification Of Wireless LAN Network Service Quality Using The Naive Bayes Algorithm In The Department Of Informatics and Computer Engineering, Faculty Of Engineering, State University Of Makassar - Siti Justianti Muhajriyah; Ruslan; Firdaus (Jurnal Komputer, Informasi dan Teknologi, 2024)
This study aims to determine the Quality of Service outcomes and the classification results of the Naive Bayes Algorithm on the Wireless LAN network quality in the Department of Informatics Engineering and Computer Faculty of Engineering at Makassar State University. This study uses the Action Research method with a quantitative approach. It conducts 54 tests using Wireshark in two different sessions to be compared for each time conducted during the research. The results of the research indicate that the status of the Wireless LAN network in the Department of Informatics Engineering and Computer Faculty of Engineering at Makassar State University falls into the "Good" category with the highest value of 59.26% , with an algorithm accuracy of 65.43%. Both testing sessions, morning session from 08:30 to 09:00 and afternoon session from 13:30 to 14:00, are categorized as "Good" according to the TIPHON standardization category as well as based on the Naive Bayes Algorithm classification results. Based on the research findings, it is recommended that the measurement of network service quality can utilize software other than Wireshark and increase the amount of test data to improve the accuracy of the Naive Bayes algorithm.